2009
DOI: 10.1111/j.1420-9101.2008.01675.x
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic analysis of microsatellite variation of guppies (Poecilia reticulata) in Trinidad and Tobago: evidence for a dynamic source–sink metapopulation structure, founder events and population bottlenecks

Abstract: Riverine fish populations are traditionally considered to be highly structured and subject to strong genetic drift. Here, we use microsatellites to analyse the population structure of the guppy (Poecilia reticulata), focussing on the headwater floodplain area of the Caroni drainage in Trinidad. We also analyse the population genetics of guppies in the Northern Drainage in Trinidad, a habitat characterized by rivers flowing directly into the sea, and a small isolated population in Tobago. Upland Caroni populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
138
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(168 citation statements)
references
References 69 publications
24
138
1
Order By: Relevance
“…These migrants may be homozygous for alleles that are rare in the recipient downstream population, resulting in the observed heterozygote deficiency. Consistent with this explanation is the study by Barson et al (2009), who showed that the lowland Caroni populations also had a heterozygote deficit at highly polymorphic microsatellite markers that they explained by the inflow of migrants from upstream populations when the rivers were in spate during the wet season rains (van Oosterhout et al, 2007;McMullan and van Oosterhout, 2012).…”
Section: Divergent Selection For Opsin Genessupporting
confidence: 61%
See 3 more Smart Citations
“…These migrants may be homozygous for alleles that are rare in the recipient downstream population, resulting in the observed heterozygote deficiency. Consistent with this explanation is the study by Barson et al (2009), who showed that the lowland Caroni populations also had a heterozygote deficit at highly polymorphic microsatellite markers that they explained by the inflow of migrants from upstream populations when the rivers were in spate during the wet season rains (van Oosterhout et al, 2007;McMullan and van Oosterhout, 2012).…”
Section: Divergent Selection For Opsin Genessupporting
confidence: 61%
“…The allele frequencies differed among populations and the differences were notably larger between the Northern/Caroni drainages of Trinidad (LY, UA, LA, UG and LG) and the other populations (Figure 2). The opsin genes in the downstream populations (LA, LG and LY) were more polymorphic than those in the upstream population (UA and UG; Figure 2 and Supplementary Tables S4 and S5) that is consistent with the higher level of genetic drift and genetic isolation found in upland regions (Barson et al, 2009;Willing et al, 2010). The SWS2-B opsin gene was highly polymorphic and the allele compositions differed among the streams.…”
Section: Overall Nucleotide Variation In Opsin Genessupporting
confidence: 55%
See 2 more Smart Citations
“…Compensatory upstream migration in the lowlands may allow the return of displaced fish that have not been swept over such barriers (see Barson et al 2009, Willing et al 2010). In addition, distinct differences exist in predator and parasite faunas between upland and lowland habitats (Endler 1980, Reznick et al 2001.…”
Section: Discussionmentioning
confidence: 99%